Inflammatory and Toxic Myopathy - Teener, James W. (Seminars in Neurology, 2012)
Although muscle diseases are relatively rare, several treatable myopathies must be recognized by the clinician to maximize the possibility of restoring strength in affected patients. The inflammatory myopathies, including polymyositis, dermatomyositis, inflammatory necrotizing myopathy, and myositis in association with mixed connective tissue disease, typically respond well to immunosuppressive treatment. Inclusion body myositis, a myopathy that has features of both inflammation and primary degeneration, may not be treatable at this time, but treatments are actively being sought. Muscle dysfunction caused by toxins must also be recognized because removal of the offending toxin usually results in restoration of normal muscle function. Important muscle toxins include cholesterol-lowering medications, colchicine, zidovudine, corticosteroids, emetine, and ethanol.
Keywords: myositis; polymyositis; dermatomyositis; inclusion body myositis; necrotizing myopathy; toxic myopathy; cholesterol-lowering agent myopathy